Can telemedicine hear the patient? interactional asymmetry, symptom narration, and diagnostic uncertainty in Indonesian virtual consultations - Mostafa Shaban (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Indonesia’s rapid normalization of telemedicine has widened access to medical contact while intensifying concern over whether platform-mediated consultation can adequately receive patient experience, symptom ambiguity, and diagnostic concern. Objective: This study examines how interactional asymmetry, symptom narration, and diagnostic uncertainty are organized in Indonesian virtual consultation discourse. Method: A qualitative corpus-based discourse-pragmatic design was applied to 20 public and verifiable telemedicine documents from government institutions, health platforms, hospital websites, app pages, and public consultation materials, coded through asymmetry mapping, symptom-narration analysis, and diagnostic-closure analysis. Results: Findings show that virtual consultation access is structured by institutional eligibility, platform routing, doctor selection, payment, emergency exclusion, and professional interpretation, positioning patients as active users whose agency remains procedurally constrained. Patient symptoms are made clinically usable through complaint prompts, uploaded evidence, symptom-checking tools, medical histories, and consultation summaries, yet extended illness chronology and contextual experience receive less visible space than short platform-ready entries. Implication: Diagnostic uncertainty is managed through referral, provisional recommendation, prescription pathways, safety boundaries, evidence requests, and digital non-substitution disclaimers, indicating that telemedicine offers guidance while preserving limits of remote clinical judgment. Novelty: This study contributes a discourse-pragmatic account of Indonesian telemedicine as mediated listening architecture where access, narration, and uncertainty are co-produced within platformed clinical communication.